(untitled) (Anclajes, 2011)
Augusto Roa Bastos introduces some modifications in the second version of Hijo de Hombre, which exhibit the author’s worries to create a transcultural narrative project, determined by the linguistic duality that characterizes the Paraguayan national territory. In agreement, a series of textual operations and narrative procedures will contribute to embody the impression of oral discourse that guaraní instills into the Spanish writing.